Progression, behavior, and intervention of dentigerous cyst: A case report and literature review - MK Saad Ali; Haya Mohammed Alfaleh; Imtenan Nasser Alnasser (Saudi Journal of Oral Sciences)
A dentigerous cyst is a developmental odontogenic cyst frequently associated with lower third molars, upper canines, and lower second premolars. In most cases, dentigerous cysts are present asymptomatically. The growth is gradual and when it reaches a significant size, it may affect anatomical structures and adjacent teeth. The majority of these cysts are detected during regular radiographic examination. They are induced by the degeneration of the enamel organ’s stellate reticulum, which results in fluid accumulation between the crown and the reduced enamel epithelium. In the presented case, we report the progression of a dentigerous cyst associated with an impacted left mandibular third molar. The cyst behavior, differential diagnosis, and management are discussed.